Mobile Reservation System for UUM INN - Fouad, Luma M. (2008)
Cell phones (mobile telephones) have today become part of our life style. One exciting thing about mobile devices is their ability to connect to the Internet and to execute web applications. Mobile applications can now be developed to deliver any types of data, to any user, any place in the world. Different mobile devices support different programming languages. Some support WAP and WML, some support HTML or a limited version of HTML, and some support both or a different language. To support all types of mobile devices, developers must create one different application for each languqge. WAP (Wireless Application Protocol) is a protocol for accessing information and services from wireless devices such as Mobile Phones and PDAs. This research introduces a prototype" MOBILE RESERVATION SYSTEM FOR UUM INN" which is a WAP application that can be used by mobile phones. The proposed application will be used to enable student or their family or any one who want to stay in UUM INN. To use their hand phone Any where any time to make reservation with the hotel.